The effects of element Cu on the electrochemical performances of Zinc-Aluminum-hydrotalcites in Zinc/Nickel secondary battery. (20th October 2015) - Wen, Xing; Yang, Zhanhong; Xie, Xiaoe; Feng, Zhaobin; Huang, Jianhang
Abstract: Zn-Cu-Al-CO3 layered double hydroxides (LDHs) have been successfully synthesized by using the method of constant pH co-precipitation. And it also has been proposed as a novel anodic material in Zinc-Nickel secondary batteries. The X-ray diffraction (XRD) patterns and scanning electron microscopy (SEM) images of the as-prepared sample exhibit that the samples are well crystallized and have hexagon structure. The electrochemical performances of Zn-Al-LDHs and Zn-Cu-Al-LDHs with different Zn/Cu/Al molar ratios are investigated by the measurements such as galvanostatic charge-discharge, cyclic voltammogram and electrochemical impedance spectroscopy (EIS). Comparing with the pure Zn-Al-LDHs, Zn-Cu-Al-LDHs show more stable cycling performance, exhibit better reversibility and display lower charge-transfer resistance. Especially, the Zn-Cu-Al-LDHs with the Zn/Cu/Al molar ratio being 2.8:0.2:1 exhibits the best electrochemical properties than other samples. After 800 cell cycles, the specific discharge capacity of Zn-Cu-Al-LDHs with the Zn/Cu/Al molar ratio of 2.8:0.2:1is 345 mA h g −1, while that of pure Zn-Al-LDHs is only 177 mA h g −1 . Based on these observations, the prepared Zn-Cu-Al-LDHs may be a promising anode active material for Zinc/Nickel secondary batteries.